Li0.5Na0.5AlB2O4F2: Fluoroaluminoborate with Aligned 1∞[BO2] Chain Induced by Unprecedented [AlO3F3]6− Species Features Enhanced Birefringence. Issue 2 (17th November 2022) - Yan, Ziting; Chu, Dongdong; Zhang, Min; Yang, Zhihua; Pan, Shilie
Abstract: Birefringent materials have been used extensively owing to their indispensable role in creating and modulating polarized light, while birefringent materials for deep ultraviolet (DUV, λ < 200 nm) applications are still urgently needed. Herein, a strategy to induce the formation of birefringence‐active 1 ∞ [BO2 ] chains driven by AlO m F n units is proposed for designing DUV birefringent materials, and a new fluoroaluminoborate, Li0.5 Na0.5 AlB2 O4 F2, with aligned 1 ∞ [BO2 ] chains and an unprecedented [AlO3 F3 ] 6− motif is synthesized. The birefringence of Li0.5 Na0.5 AlB2 O4 F2 achieves significant enhancement compared with maternal structure LiAlB2 O5 due to the optimization of functional units and arrangement via co‐substitution and fluorination tactics. The design strategy provides a propitious and feasible way to construct novel structures with excellent optical properties. Abstract : A potential deep‐ultraviolet birefringent crystal, fluoroaluminoborate Li0.5 Na0.5 AlB2 O4 F2, with aligned 1 ∞ [BO2 ] chains and enhanced properties is rationally designed and synthesized by introducing unprecedented [AlO3 F3 ] 6− motif.